Threshold voltage compensation 6T2C-pixel circuit design using OTFT for flexible display. (August 2020) - Pal, Shagun; Kumar, Brijesh
Abstract: In this paper, an internal-circuit-compensation technique is proposed to improve the threshold-variation in the pixel circuit design using OTFTs for Flexible-displays. This pixel circuit design consists of six-transistors and two-storage-capacitors (6T2C), wherein five-transistors are used as the switching elements and one-transistor is employed as driver. The proposed pixel-circuit is capable not only to compensate the threshold-variations of driving thin-film-transistors (TFTs) efficiently but also to overcome the issue of mobility-variation-degradations of the circuit caused by the large-current-error. Additionally, two-conventional-transistors-one capacitor (2T1C) based pixel-circuit is analyzed and compared with the proposed 6T2C pixel-circuit as well. The obtained results indicate that the average ​- ​value of the current-error-rate is of 6.3% as the threshold-voltage varies by ±0.03 ​V, which is much lower than that of the conventional-2T1C-pixel-circuit. The maximum OLED current of the proposed-pixel-circuit is 2.45 ​μA that can be efficiently used in the small-screen-displays. Furthermore, the proposed-circuitry is analyzed to reduce the impact of the mobility-variation on the performance of the OLED-current to improve the display-performance.